The role of computers in support of learning processes - Tiong, Chui Huong. (2009)
In our current information age, there has been an increased emphasis on the importance of bringing computers into our classrooms. This study examines how this can be achieved effectively by identifying the learning processes that lead to successful learning, and then by determining how computers support these learning processes.